SATIRICAL TECHNIQUES AND ARTISTIC STRUCTURE IN EVELYN WAUGH'S STORIES - Dilnoza Kholnazarova Rustam qizi; Mukadas Murodova Ikromovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:This article provides a detailed examination of Evelyn Waugh’s use of satire in his short stories, with particular attention to his narrative structure, stylistic choices, and tonal strategies. It argues that Waugh deliberately avoids emotional excess and overt judgment, favoring a minimalist and understated approach that heightens the satirical effect. Through examples from stories like “Mr. Loveday’s Little Outing,” “The Balance,” and “Basil Seal Rides Again,” the article illustrates how Waugh’s calm, dry tone and structured plot development subtly expose hypocrisy, vanity, and social inertia. The analysis further highlights how Waugh's satire relies on contrast between appearance and reality, speech and action, rather than direct criticism. The research  draws  from  both  Russian  and  English  literary  criticism,  demonstrating Waugh’s unique position in the tradition of English secular satire.